Adjunct Instructors: Genesis of a Continuing Professional Development Program - Claudia Gómez-Palacio; Sandra Milena Álvarez-Espinal; Deisa Enid Gómez-Vargas (Ikala: Revista de Lenguaje y Cultura, 2018)
Professional development programs (PDP) at the university level have been designed for full-time professors with the aim of enhancing their knowledge and practices. However, PDP programs focused on adjunct foreign language (AFL) instructors are not usually developed because of time, space, and contract constraints. In this article, we present a PDP that resulted from program restructuring targeting AFL instructors in a specific section at a public university in Colombia. The program is guided by a practical-critical paradigm and is divided into four “families of models” adapted from Joyce & Calhoun (2010): individual support, construction of personal and professional service, social knowledge, and instructional and curricular initiatives. Each model comprises many strategies, including the following: selection, induction, mentoring, peer-coaching, coaching, study groups, communities of practice, chats, training sessions, teacher portfolios and action research. The aim of the program is to promote the participation and involvement of AFL instructors for the enhancement of informed practices and experiences based on theory and enriching relationships with administrators and among colleagues.